On winning probabilities, weight categories, and home advantage in professional judo - Krumer, A. (Journal of Sports Economics, 2017)
Judo is a combat sport with seven different weight categories. In this article, we examined data from 1,902 men`s and 1,400 women`s fights at the eight most prestigious judo tournaments during the period 2010-2013. Using a single fight as the unit of observation, we found that the probability for the favorite to win against the underdog in the men`s half-lightweight category is significantly lower than in most other categories. Moreover, in fights in which only European and/or Asian judokas participate, we found that the men`s half-lightweight category is significantly more balanced than all other men`s categories. For women, there is no consistent evidence that any one weight category is more balanced than any of the others. Our results indicate that in choosing the members of a national team, it is to some extent reasonable for national coaches to select a lower ranked judoka in the men`s half-lightweight category over a higher ranked judoka in several other weight categories. We also found that the home advantage increases the probability of winning a single fight for both genders. This result implies that it might be worthwhile for national judo associations to bid to host international tournaments in order to improve the world rankings of their domestic judokas.